2021
DOI: 10.1111/nph.17631
|View full text |Cite
|
Sign up to set email alerts
|

A test of Sensory Drive in plant–pollinator interactions: heterogeneity in the signalling environment shapes pollinator preference for a floral visual signal

Abstract: Sensory Drive predicts that habitat-dependent signal transmission and perception explain the diversification of communication signals. Whether Sensory Drive shapes floral evolution remains untested in nature. Pollinators of Argentina anserina prefer small ultraviolet (UV)absorbing floral guides at low elevation but larger guides at high. However, mechanisms underlying differential preference are unclear. High elevation populations experience elevated UV irradiance and frequently flower against bare substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Bukovac et al (2017) modelled flower salience against more than 500 natural backgrounds and found that background colour has the potential to significantly change a flower's colour contrast. A recent study by Finnell and Koski (2021) showed that bee and fly colour preferences for ultraviolet flower markings depends on the type of background, though this preference difference depended on chromatic and not achromatic properties. The findings from Menzel et al (1997) that desert plants exhibit lower achromatic contrast than plants in the Mediterranean due to differences in background and not flower colour also suggests that achromatic aspects of backgrounds are important.…”
Section: Do Chromatic and Achromatic Cuesmentioning
confidence: 99%
“…Bukovac et al (2017) modelled flower salience against more than 500 natural backgrounds and found that background colour has the potential to significantly change a flower's colour contrast. A recent study by Finnell and Koski (2021) showed that bee and fly colour preferences for ultraviolet flower markings depends on the type of background, though this preference difference depended on chromatic and not achromatic properties. The findings from Menzel et al (1997) that desert plants exhibit lower achromatic contrast than plants in the Mediterranean due to differences in background and not flower colour also suggests that achromatic aspects of backgrounds are important.…”
Section: Do Chromatic and Achromatic Cuesmentioning
confidence: 99%
“…Sensory signaling is one of the underlying factors mediating the attraction of pollinators to flowering plants, thereby leading to the establishment of biotic interactions and ecological networks (Finnell & Koski, 2021; Sun et al, 2018). These intrinsic signals, which may be visual or olfactory, determine which pollinators are attracted to which plant species based on the signal receptive ability of the pollinators (van der Kooi et al, 2021).…”
Section: Factors Influencing Degree Of Functional Trait Matching Betw...mentioning
confidence: 99%
“…Different altitudes also vary in ambient light and background. In Colorado (USA), ambient UV light increased with altitude and different altitudes had different backgrounds (foliage or bare), which impacted the conspicuity and preference for fly and bee pollinators (Finnell & Koski 2021).…”
Section: Signaling Environmentmentioning
confidence: 99%